Pengaruh Perilaku Konsumen Muslim dalam Memilih Produk Halal Terhadap Pertumbuhan Ekonomi (Studi Kasus Pada Industri Makanan dan Minuman) - Adha, Delly Anida; Madalina, Rina; Hendra, Joni (Yayasan Rahmat Islamiyah, 2024)
This study examines the influence of Muslim consumer behavior toward halal products on economic growth, focusing on the food and beverage industry. Halal products are a vital part of Muslim consumer lifestyles, and demand for them has grown steadily over time. This research aims to identify how consumer awareness and preference for halal products affect the growth of this industry and its impact on the broader economy. The study employs a qualitative descriptive method, using a case study approach in the food and beverage industry. Data were collected through interviews and literature reviews to reveal the relationship between consumer behavior and the economic dynamics of the sector. The findings show that the increased demand for halal products not only strengthens the food and beverage industry but also contributes significantly to local economic growth.